2022
DOI: 10.1002/hep4.1941
|View full text |Cite
|
Sign up to set email alerts
|

Mac‐2‐binding protein glycan isomer predicts all malignancies after sustained virological response in chronic hepatitis C

Abstract: Despite reports of hepatocellular carcinoma (HCC) in patients with chronic hepatitis C virus (HCV) infection after achieving sustained virological response (SVR), only few studies have demonstrated the incidence of other (non‐HCC) malignancies. This study aimed to clarify the incidence, survival probability, and factors associated with malignancy, especially non‐HCC malignancies, in patients with chronic HCV infection after achieving SVR. In this retrospective study, records of 3580 patients with chronic HCV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This new discovery, the Fib-4 index, which is known to reflect the degree of progression of liver fibrosis, significantly correlates not only with HCC incidence but also with all mortality rates. In contrast, regarding non-HCC malignancies, their incidence did not increase significantly, even in the high Fib-4 group, although we previously reported that M2BPGi measurements at baseline and SVR12 may help predict the post-SVR incidence of non-HCC malignancies in patients with chronic HCV infection who achieved SVR following DAA treatment [13,15]. Moreover, similar analyses of deaths, excluding those due to malignant tumors, did not exhibit a significant difference.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This new discovery, the Fib-4 index, which is known to reflect the degree of progression of liver fibrosis, significantly correlates not only with HCC incidence but also with all mortality rates. In contrast, regarding non-HCC malignancies, their incidence did not increase significantly, even in the high Fib-4 group, although we previously reported that M2BPGi measurements at baseline and SVR12 may help predict the post-SVR incidence of non-HCC malignancies in patients with chronic HCV infection who achieved SVR following DAA treatment [13,15]. Moreover, similar analyses of deaths, excluding those due to malignant tumors, did not exhibit a significant difference.…”
Section: Discussionmentioning
confidence: 76%
“…SVR, sustained virologic response. and SVR12 may help predict the post-SVR incidence of non-HCC malignancies in patients with chronic HCV infection who achieved SVR following DAA treatment [13,15]. Moreover, similar analyses of deaths, excluding those due to malignant tumors, did not exhibit a significant difference.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to laying down ECM to promote hepatic fibrosis, these activated HSCs also secret M2BPGi, which serves as the juxtacrine-acting messenger to Kupffer cells during hepatic fibrogenesis [ 20 ]. Because there is a strong link between serum M2BPGi and hepatic fibrogenesis, studies have shown that serum M2BPGi levels are associated with fibrosis stage, dynamic fibrosis evolution, antiviral responses, presence of esophagogastric varices, risk of HCC occurrence or recurrence, extrahepatic malignancy, and survival in patients with HCV infection [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%